Visual Expression as a Language of Culture: A Case Study of Nuzi Cylinder Seal Impressions - Rosansky, Lynne Hollingshead (1984)
Ph.D. dissertation; Major Professor: Daniel F. McCall. Order No. DA8411048. Cf. DissAbstr 42/2 (1984) 568-A.